K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 7 2018

a) (a2 - 1)3- ( a4 + a2+1)(a2-1)

= (a2 - 1)3 - (a2 - 1)3 =0

b) (a4 - 3a2+ 9)(a2+3) - (3+a2)3

= (3+a2)3 - (3+a2)3

=0

17 tháng 12 2017

a,\(a^3+3a^2+4a+12\)

\(=\left(a^3+3a^2\right)+\left(4a+12\right)\)

\(=a^2\left(a+3\right)+4\left(a+3\right)\)

\(=\left(a^2+4\right)\left(a+3\right)\)

1: =(4x-1)^2-3(4x-1)

=(4x-1)(4x-1-3)

=4(x-1)(4x-1)

2: =-8x^4y^5(2y+3x)

3: =(a-5)^2-4b^2

=(a-5-2b)(a-5+2b)

5: =x^2-mx-nx+mn

=x(x-m)-n(x-m)

=(x-m)(x-n)

6: =(4a^2-3a-18-4a^2-3a)(4a^2-3a-18+4a^2+3a)

=(-6a-18)(8a^2-18)

=-6(2a-3)(2x+3)(a+3)